The Effect of Emotion Regulation Competency on Maladaptive Daydreaming among Young Adults; Mediating Role of Psychological Flexibility (Journal of Asian Development Studies, 2026)
Young adulthood is a transitional phase characterised by various personal, social, and academic challenges. During this period, skills such as Emotion Regulation Competency (ERC) and Psychological Flexibility (PF) are crucial for addressing transitional challenges. Lack of these skills raises the vulnerability to mental health challenges, including maladaptive behaviours like Maladaptive Daydreaming (MD). This study aims to examine the effect of ERC (across both negative and positive emotions) on MD, with PF mediating this relationship. Methods: Data were collected from 260 young adults (130 men, 130 women). Participants completed self-report measures, including the Perth Emotion Regulation Competency Inventory (PERCI), the Maladaptive Daydreaming Scale (MDS-16), and the Acceptance and Action Questionnaire (AAQ II), to assess ERC, MD, and PF, respectively. The collected data was analysed through SPSS. Results indicated significant associations among difficulties in emotion regulation, MD, and PF with poor ERC, resulting in higher MD and reduced PF. Additionally, mediation analyses showed that PF significantly mediates the effects of poor ERC on MD. Moreover, 64.23% of the participants were identified as maladaptive daydreamers due to experiencing MD at a significant level, suggesting a high prevalence of MD among young adults. Conclusion: Interventions aimed at enhancing emotion regulation skills and psychological flexibility can help to reduce maladaptive daydreaming and promote better mental health outcomes in young adults.